Studies on formation of the radially-directed electron beam generated by the magnetron gun with a secondary emission cathode - Ayzatsky, M.I.; Dovbnya, A.N.; Mazmanishvili, A.S.; Reshetnyak, N.G.; Romas’ko, V.P.; Chertishchev, I.A. (Вопросы атомной науки и техники, 2016)
Results are reported from the experimental and model investigations of the formation of a radially-directed electron beam, which is generated by a secondary-emission cathode magnetron gun in the electron energy range between 30 and 65 keV, as the beam is transported in the decreasing magnetic field of the solenoid. The beam transport was realized in the system consisting of copper rings with an internal diameter of 66 mm; the system was at a distance of 85 mm from the magnetron gun edge. The radial beam current and its distribution along the length of the measuring ring system were investigated versus the amplitude and gradient of the magnetic field. Studies were made into the mode of electron current bunch formation. Numerical simulation data on the tubular electron flux motion in the decreasing magnetic solenoidal field are presented. яПриведены результаты исследований и моделирования по формированию электронного пучка в радиальном направлении магнетронной пушкой с вторично-эмиссионным катодом в диапазоне энергий электронов 30…65 кэВ при транспортировке его в спадающем магнитном поле соленоида. Транспортировка пучка осуществлялась в системе, состоящей из медных колец с внутренним диаметром 66 мм, находящейся на расстоянии 85 мм от среза магнетронной пушки. Изучена зависимость тока пучка в радиальном направлении и его распределение вдоль длины колец измерительной системы от амплитуды магнитного поля и градиента спада поля. Исследован режим формирования сгустков электронного тока. Приводятся результаты численного моделирования по движению трубчатого электронного потока в спадающем магнитном поле соленоида. Приведено результати досліджень і моделювання по формуванню електронного пучка в радіальному напрямку магнетронноюгарматою з вторинно-емісійнимкатодом у діапазоні енергій електронів 30…65 кеВ при транспортуванні його в спадаючому магнітному полі соленоїда. Транспортування пучка здійснювалося в системі, що складається з мідних кілець з внутрішнім діаметром 66 мм, що знаходиться на відстані 85 мм від зрізу магнетронної гармати. Вивчена залежність у радіальному напрямку струмупучка і його розподіл уздовжкілець вимірювальної системи від амплітуди магнітного поля і градієнта спаду поля. Досліджено режим формування згустків електронного струму. Наведено результати чисельного моделювання за рухом трубчастого електронного потоку в спадаючому магнітному полі соленоїда.